The feasibility and appeal of design inspiration based on Lingnan cultural heritage in the modern elderly fashion market / Lan Mo ... [et al.] - Mo, Lan; Aris, Asliza; Zur, Rohana; Luo, Muying (College of Creative Arts, 2024)
This study explores the feasibility and appeal of infusing Lingnan cultural heritage into modern elderly fashion in China's "silver economy," targeting the unique preferences of an ageing population. The study used a quantitative research approach to collect 402 valid questionnaires from urban Chinese women aged 50-75, analyzing their fashion preferences and purchasing behaviours. The results demonstrate a significant correlation between cultural preferences, buying motivations, and buying behaviour, underscoring the role of cultural identity in elderly fashion choices. The study concludes that integrating Lingnan cultural heritage into fashion design can effectively meet the aesthetic and cultural needs of elderly consumers, fostering innovation and sustainable development in the fashion industry.